Dual chaos encryption for color images enabled in a WGM–random hybrid microcavity. Issue 31 (26th July 2022) - Zhai, Tianrui; Yan, Jiuhu; Shi, Xiaoyu; Ruan, Jun; Tong, Junhua; Liang, Ningning
Abstract : A fibrous internally integrated WGM–random hybrid cavity is first proposed, in which WGM and random lasing modes can coexist and interplay. Their free transformation provides an advanced dual chaotic image encryption system for color images. Abstract : Chaotic cryptography as an important means for digital image encryption has become a great cryptographic project in the current information age. As a novel microcavity laser, a random laser (RL) has a natural advantage for a chaotic system, relying on its spectral randomness. Nevertheless, this encrypted image generally suffers from outline exposition when an unsuitable key from a single RL spectrum is employed. Herein, to realize reliable dual chaotic encryption, an internally integrated hybrid microcavity in random and whispering-gallery-mode (WGM) is reported. Within this coupled microcavity, the rhodamine-6G-doped inner-wall of the fiber serves as the gain medium and the optical cavities for WGM lasing; an RL mode is enabled by scattered particles and the gain medium (Rh6G). Interestingly, the smooth inner wall of the fiber with a high-quality ( Q ) factor and tight optical confinement make WGM lasing occur earlier than RL. What is more, a fast energy transfer process from the WGM laser to Ag nanoparticles and the resultant localized surface plasmon resonance effects from Ag NPs to RL jointly promote the output of the random laser. As a result, a free transformation from the WGM laser to RL is successfully modulated by varying the pump power alone, thus providing two initial values for dual chaos image encryption. This work provides an in-depth understanding of a WGM–random inner-coupled cavity and promotes the application of a hybrid microcavity in the field of information security.